Tax Liability Side Equivalence in Gift-Exchange Labor Markets - Arno Riedl; Jean-Robert Tyran (Tinbergen Institute, 2003)
Tax Liability Side Equivalence (tax LSE) claims that the statutory incidence of a tax is irrelevant for its economic incidence. In gift-exchange labor markets, firms provide a gift to workers by paying high wages, and workers reciprocate by providing high efforts. Tax LSE is theoretically predicted to hold in gift-exchange markets if workers' effort choices exclusively depend on the net wage, but breaks down if they partially depend on the gross wage paid to workers. We experimentally test tax LSE in a gift-exchange market and find that it holds surprisingly well.
Keywords: C92; H22; J41; 330; Tax incidence; Efficiency wages; Gift exchange; Experiments; Steuerinzidenz; Effizienzlohn; Geschenk; Test; Theorie